Recommendation System for Giving Scholarships to New Students Using TOPSIS Method - Nuri Guntur Perdana; Muhammad Akid Musyafa; Elvanisa Ayu Muhsina; Shofwatul Uyun (IJID (International Journal on Informatics for Development), 2015)
Yayasan Pondok Pesantren Wahid Hasyim (YPPWH) is one of the bases of modern Islamic education in Daerah Istimewa Yogyakarta (Special Region of Yogyakarta). As one of devotion to education and society, formal education institutions, namely Madrasah Ibtidaiyah (Religion Elementary School), Madrasah Tsanawiyah (Religion Junior High School) and Madrasah Aliyah (Religion Senior High School) Wahid Hasyim currently have scholarship opportunities for students who excel and underprivileged, especially those from the local population. With the increasing number of scholarship applicants, making a challenge for the manager of the agency to be able to give a correct decision, effective and efficient in data management Fellow truly eligible to receive a scholarship. This study uses a Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The criteria used in these systems vary according to the scholarships provided by the Foundation. Based on the results of case selection calculations show that the results using the same system with manual calculations. The system is able to provide scholarships recommendation. This system has been passed fit for use for 100% testing of system functionality using the alpha test, the test results and accessing interface produces 65.15% of the respondents strongly agreed with the system interface, as well as the results of the test content for the page admin, counseling teachers and students each yield 88.89%, 83.33% and 100% of respondents stated strongly agree with making this system.